Genetic polymorphisms linked to coronary artery disease are not associated with carotid artery intima-media thickness, left ventricular size, or intermediate risk phenotypes. (22nd September 2015) - Cunnington, MS; Mayosi, BM; Hall, DH; Avery, PJ; Farrall, M; Vickers, MA; Watkins, H; Keavney, B
Abstract : Background: A number of single nucleotide polymorphisms (SNP) hasbeen robustly associated with coronary artery disease (CAD) in genome-wide studies, but the mechanisms of these associations are unknown. A relationship of these SNP to other cardiovascular phenotypes may give mechanistic clues. Carotid artery intima-media thickness (CIMT) is a subclinical marker of atherosclerosis associated with stroke. We investigated the association of reported CAD risk variants with CIMT, and with other intermediate risk factors and cardiovascular phenotypes that may implicate causative pathways. Methods: We studied 1425 members of 248 white British families ascertained through a hypertensive proband. We genotyped CAD risk SNP on chromosomes 9p21 (rs1333049, rs7044859, rs496892, rs7865618), 6q25 (rs6922269) and 2q36 (rs2943634) using TaqMan. Adjustments were made for significant covariates (determined by linear regression) and Merlin software was used for family-based association testing. Results: Despite the documented heritability of CIMT in this population, no significant association was found between genotype at any SNP and CIMT in 846 individuals with acceptable measurements. Nor were SNP significantly associated with intermediate phenotypes including clinic blood pressure (n  =  1171), mean ambulatory blood pressure (n  =  958), body mass index (n  =  1402), waist–hip ratio (n  =  1357), serum total cholesterol (n  =  1319), C-reactive protein (n  =  1300), IL-6 (n  =  1182), tumour necrosis factor alpha (n  =  1179), leptin (n  =  1319), urine aldosterone (n  =  636), or echocardiographic measures of left ventricular mass and left ventricular cavity size (n  =  794; all p>0.05 after adjustment for multiple testing). The maximum plausible genetic effect (based on the 95% CI) associated with each SNP was estimated using linear regression models and was found to be low (<2%) in all cases, suggesting that the observed lack of association was unlikely to be due to inadequate statistical power. Conclusions: Novel variants associated with CAD are not associated with CIMT, left ventricular hypertrophy or left ventricular cavity size and do not appear to mediate the risk of atherothrombosis through the known risk factors studied.